A new genus and two new species of Saurodocus (Crustacea: Amphipoda: Melitidae) from Lizard Island, Queensland, Australia - Yerman, Michelle N.; Krapp-Schickel, Traudl (Zootaxa, 2008)
A new genus, Saurodocus gen. nov., and two new species, S. hobbit sp. nov. and S. minimarenus sp. nov. are described from Lizard Island, Queensland, Australia, collected from coarse coral sands with coral rubble in shallow water. Saurodocus belongs to the Ceradocus group — a group of genera within the Melitidae allied to Ceradocus Costa, 1853, united by a widened triangular inner plate on maxilla 2 and setation on the inner margin of the inner plates of both maxillae. The combination of an un-produced anteroventral corner on coxa 1, lack of posteroventral lobe on coxa 4 and a deeply cleft telson separates Saurodocus from all other genera in the Ceradocus group.